Problems Affecting Financial Reporting Empiric Quality Good Governance Investigation - Safkaur, Otniel; Sagrim, Yohanis (International Journal of Economics and Financial Issues, 2019)
One of the factors that triggered a lack of environmental financial reporting was caused by the application of records that were dishonest, not yet transparent and accountable effectively by various environmental government agencies in Indonesia. This study aims to determine how the application of the environmental accrual basis in accounting records in the government environment and its effect on good governance. This study uses a method of verifying causality to determine the influence between variables. The population in this study were 44 district and city governments in the provinces of Papua and West Papua. Whereas the Observation Unit is DPPKAD in 44 Provinces / Cities / Districts in the regions of Papua and West Papua. The sampling technique uses a census so that all members of the population become the study sample. The results of this study show empirical evidence that the application of the accrual basis of environmental financial reporting affects good governance resulting from financial reporting of 44 district and city governments in the provinces of Papua and West Papua. Keywords: Financial Reporting, Good Governance, environmental financial reporting JEL Classification: G2 DOI: https://doi.org/10.32479/ijefi.8468